Peningkatan Kualitas Pendidikan Melalui Kegiatan Bimbingan Belajar Gratis ditengah Pandemi COVID19 Di Desa Cikurutug - Kurniawan; Ayu Sekarwati; Eneng Dilah Dalilatur Rahmah; Setiyo Susanto; Utis (LPPM Universitas Nusa Putra, 2022)
In the midst of the Covid19 pandemic that has hit Indonesia for the past year, various activities outside the home are limited, one of which is learning activities that are usually carried out in school buildings. This makes students especially at the elementary to junior high school levels lose their enthusiasm for learning because they cannot meet and socialize with peers and teachers as usual. This KKN activity aims to improve the quality of education as well as the enthusiasm for learning for SD, DTA and SMP students who live in Cikurutug Village, Cireunghas District, Sukabumi. This activity was held in the Al-Masyad school building by observing health protocols. This activity lasts for 10 meetings with material that has been adjusted from early childhood to junior high school levels. The time of the activity is from Monday - Thursday at 10.00 to 14.00 WIB. The supervisors who are KKN participants provide guidance and understanding for students then give some assignments so that students can practice again at their respective homes. Not only general material, the tutors also helped students in learning to read the holy Koran which was held at the mosque in the Cikurutug village area by paying attention to health protocols. As a result of these activities, the students became more enthusiastic in learning. This can be seen from the enthusiasm of the students in attending tutoring activities that always arrive on time. Not only that, the students also did their assignments very well, both the assignments given by the teachers at school through the online learning system and the assignments given by the tutors. The ability of students to understand the material also increases, this is because the tutors help explain the material that is not directly understood by students. Not only for students, this activity provides lessons and is a very valuable activity for tutors, namely participants of the Nusa Putra Community Service Program because it can contribute to society, especially in the field of education.